Dilution of broiler breeder diets with oat hulls prolongs feeding but does not affect central control of appetite - Laura M. Dixon; Sarah Brocklehurst; Joe Hills; Simone Foister; Peter W. Wilson; Angus M.A. Reid; Sarah Caughey; Victoria Sandilands; Tim Boswell; Ian C. Dunn; Rick B. D'Eath (Poultry Science)
ABSTRACT: The parents of broiler (meat) chickens (ie, broiler breeders) are food-restricted until sexual maturity, ensuring good health and reproduction, but resulting in hunger. We investigated whether diets with added insoluble fiber promote satiety and reduce behavioral, motivational, and physiological signs of hunger. Ninety-six broiler breeders were fed 1 of 4 feed treatments (n = 24 per diet) from 6 to 12 wk of age: 1) a commercial diet fed to the recommended ration (R) or 2) ad libitum (AL), the same diet as R but mixed with oat hulls at 3) 20% (OH20%) or 4) 40% (OH40%). The R, OH20% and OH40% diets were approximately iso-energetic and resulted in mean 12 wk of age weights within 2.5% of each other (1.21 kg), while AL birds weighed 221% as much (2.67kg). At 12 wk of age, agouti-related protein (AGRP) expression, was, on average, more than 12 times lower in AL birds (P < 0.001) but did not differ between the fiber diet treatments and R. Pro-opiomelanocortin (POMC) expression, was, on average, over 1.5 times higher in AL birds, but was not statistically significantly affected by feed treatments (P = 0.33). In their home pens, AL birds stood/sat more, foraged less and fed more in total (P < 0.001) and OH40% birds spent longer feeding than R (P = 0.001). Motivation to forage tested by willingness to walk through water to access an area of wood shavings (without food) was not significantly affected by diet (P = 0.33). However, restricted birds were willing to cross in only 7.3% to 12.5% of tests. Mostly birds stayed on the start platform, where AL birds sat more than other treatments and OH40% birds reduced walking relative to R birds (P = 0.016). Across the behavioral and physiological measurements there was a dichotomy of effects in response to approximately iso-energetic diets differing in fiber. There were some potentially beneficial behavioral effects related to reduced foraging and walking. However, there was no evidence that these diets significantly improved physiological measures of satiety of broiler breeders.